2009
DOI: 10.1007/s00216-009-2607-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of 3,4-methylenedioxymethamphetamine (MDMA) metabolite conjugates in human, squirrel monkey, and rat plasma

Abstract: Characterizing the formation of metabolites of 3,4-methylenedioxymethamphetamine (MDMA, “Ecstasy”) in different species (rat, squirrel monkey, and human) may provide insight into mechanisms of MDMA neurotoxicity. Two prominent MDMA metabolites, 3,4-dihydroxyme-thamphetamine (HHMA) and 4-hydroxy-3-methoxyme-thamphetamine (HMMA), are conjugated with glucuronic or sulfuric acid, but reference standards are not available; therefore, quantification is only possible after conjugate cleavage. Different concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…Deconjugation was performed because prior metabolism studies demonstrated that methylone metabolites are primarily conjugated [24,25], and commercial conjugated reference standards were unavailable. HHMC and HMMC had significant decreases in concentrations when there was no hydrolysis procedure, similar to MDMA metabolites, 3,4-dihydroxymethamphetamine and 4-hydroxy-3-methoxymethamphetamine [31,32]. These results indicate that HHMC and HMMC are present in rat plasma primarily as conjugated metabolites, which coincides with previous reports [24,25,31,32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Deconjugation was performed because prior metabolism studies demonstrated that methylone metabolites are primarily conjugated [24,25], and commercial conjugated reference standards were unavailable. HHMC and HMMC had significant decreases in concentrations when there was no hydrolysis procedure, similar to MDMA metabolites, 3,4-dihydroxymethamphetamine and 4-hydroxy-3-methoxymethamphetamine [31,32]. These results indicate that HHMC and HMMC are present in rat plasma primarily as conjugated metabolites, which coincides with previous reports [24,25,31,32].…”
Section: Discussionsupporting
confidence: 90%
“…HHMC and HMMC had significant decreases in concentrations when there was no hydrolysis procedure, similar to MDMA metabolites, 3,4-dihydroxymethamphetamine and 4-hydroxy-3-methoxymethamphetamine [31,32]. These results indicate that HHMC and HMMC are present in rat plasma primarily as conjugated metabolites, which coincides with previous reports [24,25,31,32]. Protein precipitation was achieved with perchloric acid after the addition of 4-methylcatechol, which was added to reduce possible adsorption of the dihydroxy-metabolite to precipitated proteins.…”
Section: Discussionmentioning
confidence: 92%
“…Both enzymatic and acid hydrolysis were investigated. Mueller et al [28] have found that acid hydrolysis maximises cleavage of both glucuronic and sulfuric acid conjugates for MDMA metabolites in human samples. However in our hands, acid hydrolysis was found to cause a marked decrease in recovery of AM and MA and the presence of acid also interfered with the derivatization of analytes.…”
Section: Resultsmentioning
confidence: 98%
“…Total amounts (conjugated and free) of HHMA and HMMA were determined. The procedure employed for cleavage of conjugates in rat plasma has been optimized and found to be reproducible (Mueller et al, 2009b). The linear range for the method used in the present study was 20-1000 ng/ml for HHMA, HMMA, and MDMA and 10-500 ng/ml for MDA.…”
Section: Methodsmentioning
confidence: 87%